Model approach to costs and prices’management for organization’s services - Jazykbayeva , B.K. (BUKETOV BUSINESS REVIEW, 2017)
The paper considers a model approach to managing costs and prices in organizations that provide special social services. The main mechanism for pricing services in organizations that provide special social services is cost orientation adding standard profit. Cost management becomes the main tool for pricingin connection with traditionally low profitability of this sphere and low solvency of the bulk of customers. The analysis of two basic models of organization activities’business planning characterized by staff structure is shown: personnel structure planned similarly to a private Lithuanian company and personnel structure planned on the basis of the personnel composition of the elderly commune in Osakarovka and Bukhar-Zhyrau districts of Karaganda oblast. It is revealed that the proposed models of the organization’s activities can be used both in private and non-profit organizations and organizations acquiring the right of economic jurisdiction. Using different methods of allocating indirect costs to the cost of a service makes it possible to use this method’s opportunities to form a service offer with flexible price. It is determined that the flexibility of managing costs and pricing is achieved through the development of principles for including direct and indirect costs in the service price.